THE IMPACT OF CILOSTAZOL ON ARTERIOVENOUS FISTULA MATURATION IN END-STAGE RENAL DISEASE: A PROSPECTIVE RANDOMIZED CASE-CONTROL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Arteriovenous fistula (AVF) maturation failure remains a significant challenge in hemodialysis access. Cilostazol, a phosphodiesterase-3 inhibitor with antiplatelet and vasodilatory properties, may influence maturation by mitigating intimal hyperplasia and promoting vasodilation. Methods: A prospective randomized case-control study was conducted involving 132 patients with end-stage renal disease scheduled for primary AVF creation. Patients were allocated to either the cilostazol group (n=66), receiving 100 mg twice daily postoperatively, or the control group (n=66). Preoperative and postoperative assessments included duplex ultrasound to determine arterial/venous diameters and flow rates. The primary outcome was clinical maturation, defined as a palpable thrill with successful cannulation and a Doppler flow >600 mL/min. Secondary outcomes included postoperative flow parameters and complication rates. Results: Clinical maturation, evidenced by a palpable thrill, was significantly higher in the cilostazol group (93.9% vs 71.2%, p=0.0005). Postoperative AVF flow rate (323.10 ± 52.48 cm/sec vs 286.82 ± 45.80 cm/sec, p